Citizen science fast-tracks crop technologies to boost 3 million farm households’ resilience and livelihoods - Mengistu, Dejene; Hailemariam, Bogale Nigir; Melaku, Mulugeta Tilahun; Kidane, Yosef Gebrehawaryat; Fadda, Carlo (2025)
Since 2014, ex-Bioversity International's (now the Alliance of Bioversity International and CIAT) Seeds for Needs program has evaluated, selected, and disseminated over 50 varieties of major crops to over three million Ethiopian farmers. Using participatory varietal selection and crowdsourcing, the program has empowered farmers, spanning over 1.5 million hectares, with 20‒60% productivity increases, strengthened resilience, and improved food and nutrition security. The program has also increased the varietal portfolio three- to six-fold, while reducing reliance on agrochemicals. Over 31% of direct beneficiaries have been women.